Wnt signalling pathway and tau phosphorylation: A comprehensive study on known connections. (31st March 2020) - Hadi, Fatemeh; Akrami, Hassan; Shahpasand, Koorosh; Fattahi, Mohammad R.
Abstract : The Wnt pathway is the most important cascade in the nervous system; evidence has indicated that deregulation of the Wnt pathway induced pathogenic hallmarks of neurodegenerative diseases. Glycogen synthase kinase‐3β (GSK‐3β) as the main member of the Wnt pathway increases tau inclusions, the main marker in the neurodegenerative diseases. Phosphorylated tau is observed in the pre‐tangle of the neurons in the early stage of neurodegenerative diseases. The researchers always try to improve pharmacological approaches of new therapeutic strategies to the treatment of neurodegenerative diseases that are required to represent a significant entry point by understanding the theoretical interactions of the molecular pathways. In this review, we have discussed the recent knowledge about the canonical and non‐canonical Wnt signalling pathway, GSK‐3β, Wnt/β‐catenin antagonists, tau phosphorylation, and their important roles in the neurodegenerative diseases.